Pengaruh Model Project Based Learning (PjBL) terhadap Kemampuan Pemahaman Konsep pada Materi Pecahan Siswa Kelas IV SD Negeri 004 Salo - Putri Amelia; Jesi Alexander Alim; Zariul Antosa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to see the effect of the project based learning model on the ability to understand concepts in fraction material in fourth grade elementary school. This type of research is a quantitative approach and uses a quasi-experiment method. The design in this study was a nonequivalent control group design, namely using two classes, namely class IVB as the experimental class and IVA as the control class which was obtained randomly. The experimental class will be given PjBL learning model treatment and the control class will receive conventional treatment. This study gave a pre-test to both classes before giving treatment to both classes and gave a post-test to the class after receiving treatment. Based on the results of the hypothesis test data analysis that the researchers carried out, significant independent t-test results obtained for the initial and final values ​​of the experimental class and control class were 0.027. Based on these results, a significant value of 0.027 <0.05 was obtained, so Ha was accepted and Ho was rejected. Thus, it can be concluded that there is an influence of the project based learning model on the ability to understand concepts in fraction material in class IV elementary school.